Isolation, Identification and Antibacterial Susceptibility of Staphylococcus spp. Associated with the Mobile Phones of University Students - FURUHATA, KATSUNORI; ISHIZAKI, NAOTO; SOGAWA, KAZUYUKI; KAWAKAMI, YASUSHI; LEE, SHIN-ICHI; SATO, MASAHIRO; FUKUYAMA, MASAFUMI (Biocontrol Science, 2016)
From May 2014 to February 2015, 319 university students (male, n=173; female n=146) of 18 to 24 years of age who carried mobile phones or computer tablets were selected as subjects. Staphylococcus spp. were detected in 101 of 319 samples (31.7%). In the present study, 11 strains of S. aureus were isolated and identified, not all of which were methicillin-resistant Staphylococcus aureus (MRSA). Overall, 14 species were identified, with 11 strains (10.9%) of S. xylosus being isolated at the highest frequency. Following this were eight strains (7.9%) of S. cohnii and seven strains (6.9%) each of S. capitis and S. haemolyticus. Staphylococcus spp. isolation was performed with bacterial samples obtained from the mobile phones of 22 specific subjects (males, n=12; females, n=10). Staphylococcus spp. isolation was performed on days -1, 7 and 30 of the experiment. Staphylococcus spp. were positively detected one or more times in 12 subjects (54.5%). In one subject (8.3%), all three tests were positive. Furthermore, two tests were positive in three (25.0%). In the eight remaining subjects (66.7%) Staphylococcus spp. were detected only once. For the three abovementioned tests, we investigated the pulsed-field gel electrophoresis (PFGE) patterns of the strains derived from the mobile phone and from the fingers of three subjects in whom the same bacterial species were isolated twice. From the cases with similarities between strains derived from the fingers and the mobile phones and cases, with consistency in the strains derived from the mobile phone at different times, commonality was observed in the strains derived from the fingers and mobile phones along with chronological uniformity in the strains derived from the mobile phones. A total of 101 Staphylococcus spp. strains were isolated from mobile phones. According to drug susceptibility tests, 99 strains (98.0%) were found to have some degree of resistance to drugs (excluding one strain each of S. aureus and S. haemolyticus). Among these, the strain that showed the highest level of drug resistance was one strain (1.0%) of Staphylococcus spp., which showed resistance to nine drugs. The strain that showed the second highest level of drug resistance was one strain (1.0%) of S. caprea, which showed resistance to seven drugs. In this manner, the drug-resistant tendencies of Staphylococcus spp. isolated from mobile phones were observed.